A2_3 This Desk is on Fire - Hennessy, Adam; Manivannan, Shangeetha; Page, Georgina; Suller, Laura (Physics Special Topics, 2020)
This paper looks at the wasted heat energy released from laptop chargers and calculates how many would be required to burn a wooden desk. We calculated that in one hour it would require a minimum of 6.9x10^4 chargers to heat a desk to the required temperature to burn it.